The Influence of Using Quizizz Paper Mode Media on Islamic Religious Education Students Learning Outcomes at SMP - Adzis, Ahmad Fuad; Munjiat, Siti Maryam; Izzah, Neily El (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2025)
This research aims to determine the improvement in learning outcomes in Islamic Religious Education subjects by applying the Quizizz Paper Mode learning media for class VIII students at SMP Negeri 1 Talun Cirebon. This is quantitative experimental research with a Quasi-Experimental Design in the form of a one-group pretest Posttest Design. The test instruments used are pretest and posttest in multiple choices. The type of data analysis carried out is Paired Sample T-Test analysis. The results of this research show: 1) Student learning outcomes before using the Quizizz Paper Mode learning media application obtained an average score of 50.87. 2) after implementing the Quizizz Paper Mode media, student learning outcomes obtained an average score of 84.13. 3) Using the Quizizz Paper Mode learning media influences student learning outcomes at SMP Negeri 1 Talun Cirebon. This is proven by the results of the Paired Sample T-Test with a Sig value. 0.04 < 0.05, so Ha is accepted, and Ho is rejected. Based on these findings, it can be concluded that using Quizizz Paper Mode effectively improves student learning outcomes. Therefore, teachers should integrate this media into learning to improve students' academic performance.